Interaction of yeast eIF4G with spliceosome components: Implications in pre-mRNA processing events - Kafasla, Panagiota (2009)
As evidenced from mammalian cells the eukaryotic translation initiation factor eIF4G has a putative role in nuclear RNA metabolism. Here we investigate whether this role is conserved in the yeast Saccharomyces cerevisiae. Using a combination of in vitro and in vivo methods, we show that, similar to mammalian eIF4G, yeast eIF4G homologues, Tif4631p and Tif4632p, are present both in the nucleus and the cytoplasm. We show that both eIF4G proteins interact efficiently in vitro with UsnRNP components of the splicing machinery. More specifically, Tif4631p and Tif4632p interact efficiently with U1 snRNA in vitro. In addition, Tif4631p and Tif4632p associate with protein components of the splicing machinery, namely Snu71p and Prp11p. To further delineate these interactions, we map the regions of Tif4631p and Tif4632p that are important for the interaction with Prp11p and Snu71p and we show that addition of these regions to splicing reactions in vitro has a dominant inhibitory effect. The observed interactions implicate eIF4G in aspects of pre-mRNA processing. In support of this hypothesis, deletion of one of the eIF4G isoforms results in accumulation of un-spliced precursors for a number of endogenous genes, in vivo. In conclusion these observations are suggestive of the involvement of yeast eIF4G in pre-mRNA metabolism.